Time course of cigarette withdrawal symptoms while using nicotine patch during ramadan - Maarof M.F.,; Adliah Mhd Ali,; M. Makmor Bakry,; Taha N.A., (Penerbit Universiti Kebangsaan Malaysia, 2018)
Previous studies explain the time course of withdrawal symptoms among smokers pre and post quit attempt, either with or without the help of medication. Studies showed that male Muslim smokers could quit smoking during Ramadan since fasting relate to the changes in psychosomatic, daily activities and nicotine withdrawal symptoms. This study aimed to investigate the time course of withdrawal symptoms among smokers who used nicotine patch to quit smoking during fasting in Ramadan. A total of 40 eligible Muslim males who tried to quit smoking was selected and provided with smoking cessation counseling for the duration of 8 to 10 weeks while on nicotine patch. Participants level of withdrawal symptoms was recorded by using nine items of Minnesota Nicotine Withdrawal Scale over a period of 60 days. Participant’s carbon monoxide reading and body weight were measured within six months including pre and post-Ramadan fasting. Over four weeks of the fasting month, the measured withdrawal symptoms such as urge to smoke (P ≤ 0.001), depressed mood (P ≤ 0.001), irritability/frustration or anger (P ≤ 0.05), anxiety (P ≤ 0.05), difficulty concentrating(P ≤ 0.001), restlessness (P ≤ 0.001), difficulty going to sleep (P ≤ 0.001) and impatient (P ≤ 0.05) significantly decreased except appetite by the end of week 4. Time course analyses demonstrated that all outcome measures showed good effects during cessation in fasting month. The point prevalence abstinence at first month of quitting was 67.5% which is higher in fasting month. This has shown positive clinical implications in managing smoking cessation program during Ramadan with the aid of nicotine patch.